The Purple Robe Incident and the Formation of the Early Modern Sōtō Zen Institution - Williams, Duncan Ryūken (Japanese journal of religious studies, 2009)
The transition from the medieval to the early modern Buddhist order was directed in large measure by a new regulatory regime instituted by the Tokugawa bakufu. These new directives issued from Edo increasingly regulated every aspect of both political and religious life during the first half of the seventeenth century. As the bakufu extended its control over domains through a pyramidal hierarchy of order towards the center, similar formations of regulation governing Buddhist sectarian order emerged in an increasingly formalized fashion. At the same time, power did not operate in a unilateral direction as Buddhist institutions attempted to shape regulation, move toward a self-regulatory model of governance, and otherwise evade control by the center through local interpretations and implementations of law. This essay takes up how state regulation of religion was managed by Sōtō Zen Buddhism, with particular attention given to rules governing the clerical ranks and the robes worn by clerics of high rank. The 1627 "purple robe incident" is examined as an emblematic case of the new power relationship between the new bakufu's concern about subversive elements that could challenge its hold on power; the imperial household's customary authority to award the highest-ranking, imperially-sanctioned "purple robe"; and Buddhist institutions that laid claim on the authority to recognize spiritual advancement.